X-ray Microtomography as a Non-Invasive Method for Evaluating the Stability of Commercial Effervescent Tablets - Michał Meisner; Piotr Duda; Beata Szulc-Musioł; Beata Sarecka-Hujar (Engineering Proceedings, 2023)
In the present study, a non-invasive X-ray microtomography technique was applied to assess the internal structure of commercial effervescent tablets with vitamin C. Expired tablets stored under ambient conditions were analyzed and the results obtained were compared with unexpired tablets. Significantly higher density values were found for the unexpired tablets (1.250 g/cm3) compared to the expired tablets (1.242 g/cm3). The results indicate a better homogeneity of the unexpired tablets, which may affect their mechanical strength.